Competition between outer zone electron scattering by plasmaspheric hiss and magnetosonic waves. Issue 8 (30th April 2017) - Ni, Binbin; Hua, Man; Zhou, Ruoxian; Yi, Juan; Fu, Song
Abstract: We quantify the electron scattering effects of simultaneous plasmaspheric hiss and magnetosonic waves that occurred in two neighboring time intervals but with distinct wave intensity profiles on 21 August 2013. Their combined scattering is found capable of causing electron distribution variations largely distinguishable from the consequences of individual waves. The net effect of electron diffusion relies strongly on the relative dominance of the two wave intensities, which also controls the relative contribution of each wave mode. In combination, MS waves slow down the hiss‐induced loss of 100 keV electrons, and hiss efficiently inhibits the electron butterfly distribution caused by MS waves to produce a gradual acceleration process. Our results strongly suggest that comprehensive simulations of the radiation belt electron dynamics should carefully incorporate the combined scattering and complex competition resulting from simultaneous occurrences of various magnetospheric emissions, including, but not limited to, plamaspheric hiss and magnetosonic waves. Key Points: Combined scattering by hiss and MS waves results in outer zone electron variations distinct from the consequences of individual wave modes Net electron diffusion relies strongly on the relative dominance of wave intensities that also controls the relative roles of each wave mode Combined scattering and complex competition of concurrent plasma waves should be incorporated in radiation belt dynamic simulations